The spectrum and principal functions of a nonself-adjoint Sturm–Liouville operator with discontinuity conditions - Palamut Kosar, Nida; Akcay, Ozge (Eurasian Mathematical Journal, 2024)
This paper deals with the nonself-adjoint Sturm–Liouville operator (or one-dimensional time-independent Schrödinger operator) with discontinuity conditions on the positive half line. In this study, the spectral singularities and the eigenvalues are investigated and it is proved that this problem has a nite number of spectral singularities and eigenvalues with nite multiplicities under two additional conditions. Moreover, we determine the principal functions with respect to the eigenvalues and the spectral singularities of this operator.